Hubungan panjang klavikula dan tinggi badan pada mahasiswa Fakultas Kedokteran Unsrat angkatan 2012 - Liputra, Osvaldo T.; Pasiak, Taufiq F.; Wongkar, Djon (e-Biomedik, 2017)
Abstract: Clavicle is a long slender bone that lies horizontally at the root of the neck just beneath the skin. The clavicle is connected to the sternum and the first costal cartilage and acromion process of the scapula laterally. Body height is formed by the skull, vertebra column, and a part of lower limb bones. This was an analytical descriptive study with a cross sectional design. Subjects were 76 students of Faculty of Medicine University of Sam Ratulangi Manado obtained by using purposive sampling method. Data were analyzed by Pearson correlation test and linear regression test. The Pearson correlation test showed that there was a weak correlation between clavicle length and body height in males (r = 0.149) and a strong enough correlation in females (r = 0.360). The linear regression test showed the equation in males was BH (body height) = 160.042 + (0.606 x clavicle length) and in females was BH = 145.121 + (1.044 x clavicle length). Conclusion: There was a strong enough correlation between clavicle length and body height in females but not in males. Body height can be determined by clavicle length using an equation.Keywords: clavicle length, body heightÂ Abstrak: Klavikula merupakan tulang panjang yang ramping, membentang horizontal di dasar leher tepat dibawah kulit. Klavikula terhubung dengan sternum dan tulang rawan rusuk pertama, serta menyamping dengan akromion dari skapula. Tinggi badan dibentuk oleh tulang tengkorak, tulang belakang, dan sebagian tulang ekstremitas bawah. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Subyek penelitian ialah 76 orang mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi Manado yang ditentukan dengan cara purposive sampling. Data dianalisis dengan uji korelasi Pearson dan uji regresi linear. Hasil uji korelasi Pearson memperlihatkan hubungan lemah antara panjang klavikula dan tinggi badan pada laki-laki (r=0,149) dan hubungan cukup kuat pada perempuan (r = 0,360). Persamaan pada laki-laki TB = 160,042 + (0,606 x panjang klavikula) dan pada perempuan TB = 145,121 + (1,044 x panjang klavikula). Simpulan: Terdapat hubungan yang cukup kuat antara panjang klavikula dengan tinggi badan pada perempuan tetapi tidak pada laki-laki. Tinggi badan seseorang dapat ditentukan dari panjang klavikula dengan menggunakan suatu persamaan.Kata kunci: panjang klavikula, tinggi badan